The Mobile Linpack: initial experience of the performance ranking for portable devices. - Iachnik, O.O.; Nikitenko, D.A.; Sobolev, S.I. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2018)
Contemporary computing is strongly associated with parallelism. From personal tablets and phones and up to the top supercomputers, the scales and approaches differ, but the idea of work distribution is present everywhere. A study of portable platforms parallel computing capabilities was started at the Research Computing Center of Lomonosov Moscow State University several years ago, in 2014. There were Android and iOS implementations of popular benchmark developed. Four years of the test availability for regular users turned into almost 20 thousand of test results. This paper addresses the investigation of facts and trends, mined out of this data, proving the reasons for the further Mobile Linpack development.